Global, regional, and national burden and trends of syphilis among women of childbearing age from 1990 to 2021 - Huang, Yanhui; Ye, Yunfeng; Li, Limei; Zhou, Zhiheng (Frontiers in Public Health, 2025)
BackgroundSyphilis represents a significant sexual health concern for women of childbearing age (WCBA) worldwide. However, information regarded the burden and trends associated with this disease is limited. This study aimed to evaluate the changes in syphilis burden among WCBA aged 15–49 years from 1990 to 2021 at global, regional, and national levels.MethodsThe extensive information was gathered from the Global Burden of Disease (GBD) 2021 database concerning the incidence, prevalence, and disability-adjusted life years (DALYs) related to syphilis in WCBA aged 15–49 across 204 countries and territories from 1990 to 2021. To quantify temporal trends, the estimated annual percentage change (EAPC) was calculated in age-standardized rate (ASR) for incidence, prevalence, and DALYs based on age group, region, and sociodemographic index (SDI). The relationship between ASR and SDI was examined using spearman correlation analysis.ResultsIn 2021, there were 20.48 million prevalent cases, 5.36 million new syphilis cases, and 39.59 thousand DALYs among WCBA, reflecting increases of 45.85, 46.96, and 16.08%, respectively, since 1990. Over 32 years, global rates of prevalence, incidence, and DALYs declined, with EAPCs of −0.50, −0.35, and −1.30. However, high-middle SDI regions experienced rising trends in incidence (EAPC: 0.28) and prevalence (EAPC: 0.22). The Low-middle SDI region had the highest syphilis cases among WCBA, accounting for about one-third of the global total. Notably, the 20–24 age group had the highest incidence rate at 467.35 per 100,000.ConclusionOur findings highlight a decline in the global prevalence of syphilis from 1990 to 2021, the burden of this disease remains significant in low-and middle-income countries and regions. The development of more effective strategies to prevent and reduce the burden of syphilis is a pressing need.